ANALYSIS OF FACTORS THAT INFLUENCE IMPULSIVE BUYING WITH POSITIVE EMOTION AS A MEDIATOR - Lestari, Melissa; Sinambela, Fitriana Aidnilla (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
People's shopping habits had changed in today's business environment, many people make impulse purchases because of their interest in a brand or product that trending at that time. Due to that trends, people now see shopping as a necessity that must be fulfilled, they become more consumptive and make shopping as a lifestyle. The aim of research is to identify factors that influence impulsive buying. The population data used in this research were 230 respondents who used e-commerce in Batam City. Through quantitative research method, the data were tested for hypotheses by processing them with structural equation modeling analysis based on PLS. The results showed impulsive buying is influenced by positive emotion and price discount variables. Meanwhile, impulsive buying is not influenced by variables of fashion involvement, shopping lifestyle, hedonic shopping motivation, and sales promotion. However, positive emotion as a mediator role is able to mediate all variables on Impulsive Buying. The implications of the results can be applied to practitioners in adopting marketing strategies to evoke positive consumer emotions that lead to impulse purchases.